PD-1 inhibitor combined with TPF induction chemotherapy in locally advanced nasopharyngeal carcinoma: a retrospective study of efficacy and safety - Zhang, Weiwei; Meng, Yousheng; Zhang, Ping; Tian, Dujuan; Zeng, Xianghua; Dong, Mingqing; He, Lang (Frontiers in Immunology, 2025)
BackgroundThe efficacy of PD-1 inhibitors in the induction therapy of locally advanced nasopharyngeal carcinoma (LA-NPC) remains unclear. The aim of this study was to retrospectively investigate the efficacy and safety of PD-1 inhibitor combined with induction chemotherapy in patients with LA-NPC.Patients and methodsA retrospective study was conducted on 158 LA-NPC patients, 80 patients received TPF (nab-paclitaxel, cisplatin and 5-fuorouracil) induction chemotherapy, and 78 patients received TPF-ICB (TPF plus PD-1 inhibitor) chemoimmunotherapy. Treatment response was evaluated immediately following completion of induction therapy using RECIST v1.1 criteria, including cervical lymph nodes and primary nasopharynx lesions. Responses were categorized as complete response (CR), partial response (PR), stable disease (SD), or progressive disease (PD), with objective response rate (ORR) calculated as the combined CR+PR rate. Secondary endpoints included progression-free survival (PFS), overall survival (OS), and toxicity assessment. Acute treatment-related toxicities during induction therapy were graded according to CTCAE v5.0 criteria and compared between treatment groups.ResultsAfter induction therapy, the ORR in the TPF group was significantly lower than that in the TPF-ICB group (71.2% vs. 88.5%, p = 0.007). The complete response (CR) rate in the TPF-ICB group was significantly higher than in the TPF group (29.5% vs. 11.3%, p = 0.004). The 3 and 5 years PFS rates in TPF-ICB group were 99% and 95%, which were significantly higher than the TPF group (89% and 87%, both p < 0.05). The 3-year (99% vs. 89%, p <0.001) and 5-years OS rates (95% vs. 87%, p < 0.0001) were superior in the TPF-ICB group. Grade ≥3 TRAEs occurred in 7 (8.6%) and 12 (15.5%) patients in the TPF and TPF-ICB groups, respectively (p = 0.596).ConclusionsThe induction therapy of PD-1 inhibitor combined with TPF showed high CR and ORR rates in LA-NPC, and the safety was acceptable.